A study on the relationship between project management competency, job performance and job motivation in e-commerce industry. Issue 1 (2nd April 2021) - Lin, Yiching
Abstract : Purpose: This study aims to investigate the relationship between project management competency, job motivation and performance in people engaged in electronic commerce (e-commerce). A questionnaire was developed for e-commerce workers in various professional aspects including business strategy planning, content management and design, sales services, marketing business sales, host settings, analysis and management. A total of 299 valid questionnaires were retrieved. Multiple regression analysis was applied to the testing and analysis on important competences for project management and the factors influencing job performance. Design/methodology/approach: In this study, the related indexes are measured mainly through appropriate questionnaire design and the questionnaires were mainly distributed among employees and managers of the e-commerce enterprises. Tables 5–1 provide the personal profiles of the e-commerce personnel. A total of 350 questionnaires were distributed and 320 questionnaires were returned. After the 320 questionnaires were sorted and categorized, 21 incompletely-filled and invalid questionnaires were excluded, for a total of 299 valid questionnaires that were returned. Based on the quantitative data obtained from the returned valid questionnaires, files were created and statistical analyzes were conducted by the computerized statistical software statistical product and service solutions 21. According to the research question and nature of this study, the present study mainly adopted statistical methods, including descriptive statistical analysis, reliability analysis, Pearson's correlation analysis and regression analysis. Findings: The results suggested that the project management competency of those engaged in e-commerce had a positive influence on their work performance. The capabilities in the management of integration, scope and procurement were significantly important factors identified in this study. In addition, the internal and external motivations of those engaged in e-commerce had a positive influence on work performance, and thus, facilitated their influence on the project management competency. The results and statistical analysis could be a reference in e-commerce-related business management and serve as the basis for evaluation of the training of project management competencies for those engaged in e-commerce and further improvements of human capitals and corporate competitive advantages. Originality/value: This study used literature on project management competence and job performance as a foundation; previous studies argue that project management competence has a positive correlation with job performance. Empirical results reveal that among the e-commerce personnel, most dimensions of project management competence are significantly correlated with job performance. This study reveals that stakeholder management competence, the newly introduced 10th dimension of project management competence, is also significantly correlated with job performance. Therefore, study results reveal that project management competence has a significant positive correlation with job performance. In this study, the two constructs of internal motivation and external motivation in job motivation are introduced for use as disturbing factors. Empirical results reveal that internal motivation and external motivation have a significant positive disturbing effect with respect to the influence of cost management competence and human resource management competence on job performance. Hackman and Oldham (1975) contend that the jobs calling for a variety of skills can boost the job motivation of employees. Study results reveal that job motivation is of great importance to the influence of project management competence on job performance and can be used as the basis for improving job performance.